Effects of Corporate Governance on Bank Risk Taking - Magar, Dristi Thapa; Pun, Dhan Bahadur (The Lumbini Journal of Business and Economics, 2022)
This paper intends to examine the effects of corporate governance on bank risk-taking. The data from 14 commercial banks are collected by applying stratified random sampling technique for the period of 2010 to 2021. Board size, audit committee meeting, institutional ownership, CEO tenure, board meeting, and CEO age are taken as proxies for corporate governance variables, and the non-performing loan ratio is taken as a proxy for bank risk-taking. The result of unbalanced panel regression shows a significant positive effect of board size and CEO age on bank risk-taking, whereas the effect of audit committee meetings, institutional ownership, CEO tenure, and board meetings on bank risk-taking is insignificant. Therefore, it can be concluded that Nepalese commercial banks can improve their performance by keeping the board size as small as possible and hiring younger CEOs so as to avoid undesirable risk-taking.